2013
DOI: 10.1039/c3gc40297e
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous poly-melamine-formaldehyde (mPMF) – a highly efficient catalyst for chemoselective acetalization of aldehydes

Abstract: A mesoporous poly-melamine-formaldehyde polymer with a high surface area, good porosity and a high density of amine and triazine functional groups was investigated as a highly efficient hydrogen-bonding catalyst. This porous organic polymer was found to be highly effective in catalyzing chemoselective acetalization of aldehydes, without the consumption of any dehydrating agents. The turnover frequency of mesoporous poly-melamineformaldehyde is hundreds of times higher than melamine monomer, and this high effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 44 publications
4
32
0
1
Order By: Relevance
“…2B and b) and TEM ( Fig. More importantly, the similar results were also reported by Tan et al 30,31 In addition, the SEM images ( Fig. Moreover, to optimize the porosity and CO 2 adsorption characteristics, a series of MMFSs with different PFA/M molar ratios of 2.0 to 4.5 were synthesized.…”
Section: Adsorbent Characterizationssupporting
confidence: 78%
See 1 more Smart Citation
“…2B and b) and TEM ( Fig. More importantly, the similar results were also reported by Tan et al 30,31 In addition, the SEM images ( Fig. Moreover, to optimize the porosity and CO 2 adsorption characteristics, a series of MMFSs with different PFA/M molar ratios of 2.0 to 4.5 were synthesized.…”
Section: Adsorbent Characterizationssupporting
confidence: 78%
“…It was revealed that high nitrogen (N) content and surface area can result in high uptake and selectivity simultaneously. [24][25][26][27][28][29][30][31][32] However, owing to the weak selfassembly ability of precursor components and the serious cross-linking of neighboring nanospheres during the hydrothermal process, the synthesis of mesoporous melamineformaldehyde spheres (MMFSs) through a simple, low-cost and environmentally friendly method is inherently nontrivial. More importantly, melamine resins can be produced in an industrial scale and widely used as a cross-linker in organic coatings and plastics.…”
Section: Introductionmentioning
confidence: 99%
“… Organocatalytic reactions catalyzed by N‐containing Lewis bases within a) hyper‐cross‐linked high internal phase emulsion polymers,41 b) melamine‐formaldehyde resin,42 c) Tröger’s base CMP,44 d) Brønsted acids such as a HCP with carboxylic acid groups,32d and e) an aromatic framework containing amine and sulfonic acid moieties 45…”
Section: Nanoporous Polymers In Catalysismentioning
confidence: 99%
“…A simple, green, and efficient strategy for the synthesis of benzoxazoles and benzothiazoles was developed [39] by using the mesoporous poly(melamine-formaldehyde) 50 [40][41][42] prepared starting from melamine and paraformaldehyde (Scheme 22). Polymer 50 acted as bifunctional catalyst and, under the optimized catalytic conditions, led to benzoxazoles and benzothiazoles with good and excellent yields (71%-99%) by reaction of substituted 2-aminophenols with benzaldehydes using dioxygen as oxidant.…”
Section: Miscellaneous Examplesmentioning
confidence: 99%